Successful community nutrition programming: lessons from Kenya, Tanzania, and Uganda - Iannotti, Lora; Gillespie, Stuart (Regional Centre for Quality Health Care, 2002)
...This report brings together the main findings of a series of assessments of successful community nutrition programming carried out in Kenya, Tanzania, and Uganda between 1999 and 2000. The overall aim of the assessments was to identify key lessons, or the main driving forces behind the successful processes and outcomes in these programs. Such elements of success fundamentally have to do with both what was done and how it was done....The major success factors identified in these country assessments and discussed in detail in this report have been placed in the following four categories, based on the chronological phase of the community nutrition program: Process leading to program development, including role of contextual factors; Program design and content; Program management and implementation; and Evolution, sustainability, and scaling up of the program. Following a historical review of experiences with community-based nutrition programming in the region and elsewhere, the report discusses the findings of the assessment and describes the key elements of success in each of the above categories."--- from Executive Summary and Introduction.